Successful resumption of peritoneal dialysis following living donor liver transplantation in children with end‐stage renal disease. (18th February 2017) - Kanazawa, Hiroyuki; Fukuda, Akinari; Sato, Mai; Ishimori, Shingo; Sasaki, Kengo; Uchida, Hajime; Shigeta, Takanobu; Mali, Vidyadhar Padmakar; Sakamoto, Seisuke; Ishikura, Kenji; Kasahara, Mureo
Abstract: Children with ESRD in need of RRT are commonly managed by PD due to difficulty with vascular access for HD and the relatively large extracorporeal blood volume required. Major abdominal surgery may result in injury to the peritoneum and consequent adhesion, thereby resulting in a reduction in the anatomical capacity and transport capability across the peritoneal membrane. Here, we report successful resumption of PD after LDLT in two pediatric patients. The causes of ESRD were PH1 and juvenile nephronophthisis, respectively. Both patients were managed by PD prior to LDLT. PD was converted to HD starting three days before LDLT and was continued postoperatively until resumption of PD on days 13 and 28, respectively. The PD weekly Kt/V urea was maintained before and after LDLT. The patients continued to do well on PD without complications. Meticulous intra‐operative techniques during LDLT allow postoperative PD resumption by preservation of peritoneal integrity with effective transport capability and without added risk of peritonitis.